Annuity markets in Chile : competition, regulation - and myopia ? - Walker Hitschfeld, Eduardo (Policy research working paper, 2006)
"The author studies annuity rates in Chile and relates them with industry competition. He finds (1) that annuity insurance companies paying higher broker commissions paid lower annuity rates; and (2) a structural break of the long-run elasticity of annuity rates to the risk-free rate in 2001. Moreover, this structural break coincided with the submission of a new draft pension law proposing greater transparency in annuity markets and a generalized drop in broker commissions. The high commissions charged in the 1990s were partly returned to annuitants as informal (and illegal) cash rebates. Myopic pensioners preferred cash rebates over present values. Thus, the legal threat caused the drop in broker commissions, reduced the illegal practice of cash rebates, increased competition by way of annuity rates, and raised the long-run elasticity to one. "--World Bank web site